»We Are All Activists« Exploring Solidarities in Activism By, With and For Refugees and Migrants in Hamburg - Rzadtki, Lea (Soziale Bewegung und Protest, 2022)
Who is meant when people talk about the citizens or the activists? Often, they are implied to mean the most privileged positionalities. Simultaneously, refugees and migrants tend to be seen through their (supposed) legal status. Thus, they are neither practically nor conceptually regarded as activists. The variety of intersecting positionings in migrant rights activism results in complex inequalities and power dynamics within activist groups. Solidarities are continually challenged, negotiated, and built. Lea Rzadtki develops a conceptual view on claims, challenges, and processes that activists experience and deal with. She moves beyond dichotomies and engages in transversal dialogue.